Kerajaan Minangkabau Sebagai Asal-usul Kesultanan Jambi - Arif Rahim (Universitas Batanghari Jambi, 2021)
This article discusses the Minangkabau kingdom and its existence as the origin of the Jambi Sultanate. This issue is considered important because at this time there are many people who do not understand the relationship between the kingdoms in the past, which regions are currently included in the kingdoms of these kingdoms. The results of this study are expected to provide an explanation of the main problems proposed and so contribute to the development of knowledge, especially about the local history of Jambi and West Sumatra. Besides, it can be used as material for consideration by related institutions in order to preserve historical and cultural values and for regional development and development. By using a multidimensional approach and supported by the application of historical methods that refer to scientific historical research procedures, it is hoped that the questions raised in the formulation of the problem will be objectively and systematically expressed. The results showed that the Minangkabau area was an old area that had been inhabited by humans at least since the Batu Muda era around 2000 years BC. In the district of 50 Kota there are many Menhir findings which are thought to be from that period. The Minangkabau area is the area where Sang Sapurba's title Datuk Maharaja Diraja descended which in oral tradition is considered the ancestor of the Minangkabau tribe and the Malay family in general and also as a figure who descended the kings who ruled on the island of Sumatra, especially the Malay countries. In the context of Jambi and Minangkabau relations, it can be said that the kings who ruled in the Jambi kingdom were descended from the Minangkabau Kingdom. Putri Selaro Pinang Masak, who in the Jambi royal legend is seen as the founder of the Jambi kingdom, was the son of Ananggawarman who ruled in Pagaruyung from 1376 - 1417 AD. As an old country, Minangkabau has a customary and cultural system that affects the surrounding area, including the Jambi area. A source from the Jambi Malay Customary Institute said that the one who composed Jambi's customs was Datuk Perpatih Nan Sabatang from Pagaruyung, while those from Bandar Jambi were Datuk Ketemanggungan